At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
[tex]\frac{5}{\sqrt{5-2\sqrt{6}}}^{(\sqrt{5+2\sqrt{6}}}= \frac{5\sqrt{5+2\sqrt{6}}}{\sqrt{(5-2\sqrt{6})(5+2\sqrt{6})}}= \\\\\\ = \frac{5\sqrt{5+2\sqrt{5}}}{\sqrt{25-24}}= \\\\ = \frac{5\sqrt{5+2\sqrt{6}}}{1}= \\\\ =\boxed{5\sqrt{5+2\sqrt{6}}}[/tex]
[tex]5\sqrt{5+\sqrt{24}}= \\\\ A=5 \\ B=24 \\ C^2=A^2-B= 25-24=1 \ \ \ \Longrightarrow \boxed{C=1} \\\\\\ 5\sqrt{\frac{A+C}{2}+\frac{A-C}{2}}= 5\sqrt{\frac{5+1}{2}+\frac{5-1}{2}}= \\\\=5 \sqrt{\frac{6}{2}+\frac{4}{2}}= \\\\ =\boxed{\boxed{5(\sqrt{3}+\sqrt{2})}}[/tex]
[tex]5\sqrt{5+\sqrt{24}}= \\\\ A=5 \\ B=24 \\ C^2=A^2-B= 25-24=1 \ \ \ \Longrightarrow \boxed{C=1} \\\\\\ 5\sqrt{\frac{A+C}{2}+\frac{A-C}{2}}= 5\sqrt{\frac{5+1}{2}+\frac{5-1}{2}}= \\\\=5 \sqrt{\frac{6}{2}+\frac{4}{2}}= \\\\ =\boxed{\boxed{5(\sqrt{3}+\sqrt{2})}}[/tex]
[tex]5-2\sqrt{6}}=\sqrt{3}^2-2\sqrt{3}\sqrt{2}+\sqrt{2}^2=(\sqrt{3}-\sqrt{2})^2[/tex]
Hence [tex]\dfrac{1}{\sqrt{5-2\sqrt{6}}}}=\dfrac{1}{\sqrt{3}-\sqrt{2}}=\dfrac{\sqrt3+\sqrt2}{\sqrt3^2-\sqrt2^2}=\sqrt3+\sqrt2[/tex]
Therefore [tex]\boxed{\dfrac{5}{\sqrt{5-2\sqrt6}}=5(\sqrt3+\sqrt2)}[/tex]
Hence [tex]\dfrac{1}{\sqrt{5-2\sqrt{6}}}}=\dfrac{1}{\sqrt{3}-\sqrt{2}}=\dfrac{\sqrt3+\sqrt2}{\sqrt3^2-\sqrt2^2}=\sqrt3+\sqrt2[/tex]
Therefore [tex]\boxed{\dfrac{5}{\sqrt{5-2\sqrt6}}=5(\sqrt3+\sqrt2)}[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.